Pengembangan Lembar Kerja Peserta Didik (Lkpd) Berbasis Project Based Learning Siswa Kelas Iv Pada Subtema Hebatnya Cita-Citaku Sdn Ujung Ix Surabaya - Ainul Fitriyah; Nurul Agustin; Rahmat Rudianto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
This research is a product development research, namely project-based learning worksheets. The purpose of this study is to design and develop project-based learning worksheets on the Sub-theme material, My Great Aspirations class IV. Subject validation by 1 material expert, 1 media expert and 1 design expert, and 7 students to do the experiment in small groups. In this study using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). This study uses the method of observation, structured interviews, document collection, questionnaire data collection. The data analysis used is descriptive qualitative analysis and quantitative descriptive analysis. The results of the material trials showed conformity with the teaching materials in the very good category and deserved to be put into the form of project-based learning worksheets in the good category. The results of the student worksheet media validation are categorized as good, and the results of the design validation show that the LKPD displayed is attractive and suitable for use when trials and learning activities take place. The results of the respondents prove that the suitability of project based learning worksheets is in accordance with the very good category.